Characterization of the Human Immunodeficiency Virus / AIDS Epidemic in Cienfuegos. 2006- 2010 - Isis Arelis Espinosa Salas; Sara Hernández Malpica; Maitté González Vila; Mario Álvarez Gutérrez (Medisur)
Background: There was an increase in the incidence of cases diagnosed with human immunodeficiency virus / AIDS in the province of Cienfuegos during the last five years. Objective: To characterize the epidemic of human immunodeficiency virus / AIDS in the province of Cienfuegos. Method: A descriptive study of a series of cases (195) diagnosed with human immunodeficiency virus / AIDS was conducted in the province of Cienfuegos from 2006 to 2010. The variables analyzed were: age, sex, sexual orientation, source of inquiry, source of infection and municipality of origin. Results: The epidemic showed a higher incidence among homo-bisexual males aged 25 to 44 years. Most cases were detected by contact tracing. The form of infection mentioned by all cases was sexual. The vast majority of them (74.4%) ignored the source of infection. Conclusions: The epidemic has been characterized by a steady increase in incidence during the last five years, most notably in 2009 and 2010. Although there is a prioritized program for HIV/AIDS control and prevention as well as large information campaigns on this subject, the epidemic continues to affect individuals with risky behavior, as evidenced by the number of patients presenting the clinical onset of AIDS.